Cyberbullying among Malaysian youth: the case of Selangor - Saharrudin, Nurul Farhana; Ahmad Ghazali, Akmar Hayati; Abu Samah, Asnarulkhadi; Ahmad, Aminah; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2019)
This study aims to identify Selangor youth’s engagement in cyberbullying activities. The study was carried out by a cross-sectional survey of 400 youths in four districts in Selangor namely, Hulu Langat, Serdang, Sabak Bernam and Klang. The study found that Selangor youth’s engagement in cyberbullying activities to be at low level. The findings also indicated that the most common form of cyberbullying activity committed among this particular group of youth was to block others in instant messaging application such like WhatsApp, Facebook, Messenger and etc. Several recommendations are made to overcome this social problem, quite a few actions were highlighted to take into consideration such as parental monitoring, cyber education, counseling, media awareness and campaign and the role of internet providers.